دور صناعة التأمین كاستراتیجیة للتنویع الاقتصادي وتحقیق التنمیة الاقتصادیة دراسة حالة فرنسا كنموذج - جیرار, فیروز (Finance and Business Economies Review, 2018)
Economic diversification is an important strategic choice for all; developed and developing countries, rich in natural resources and those with limited ones , in which they need to continue to expand the sources of national income and to strengthen sustainable development and economic growth in general. Economic diversification does not include only the diversification of exports; especially for countries with the sole source; it may also include the development of multiple and diversed sectors as a source of national income. France is considred as one of the developed countries that has made great strides in achieving economic diversification through the orientation towards the services sector and which has become a backbone of economy in many countries of the world, especially the insurance industry, which is effectively supporting economic diversification policy of the French government, due to the prominent role played by this industry in the French economic development